Banal o makasalanan - de Guzman, Susan C.; Razon, Delia; Montenegro, Mario; de Cordova, Joseph; LVN Pictures (Firm). ([Pace of production not identified] LVN Pictures, 1955)
The story of Salome, the stepdaughter of King Herod of Judea, and how she found love and faith through the Roman centurion Cornelius.--Summary taken from https://www.imdb.com/title/tt0777760
Produced by Narcisa de Leon; music by Antonio Buenaventura.
Delia Razon, Mario Montenegro, Joseph de Cordova.
DVD
In Tagalog
Keywords: Drama